MICROSATELLITE GENOTYPING OF DON LOCAL GRAPE (VITIS VINIFERA L.) VARIETIES - E. T. Ilnitskaya; S. V. Tokmakov; I. I. Suprun (Вавиловский журнал генетики и селекции)
Local traditional varieties constitute an important portion of grape genetic resources. DNA profiles for microsatellite loci VVMD5, VVMD7, VVMD27, VVS2, VrZAG62, and VrZAG79 were obtained for 11 local grape cultivars grown in the Don region. These SSR-markers are recommended as basic for Vitis vinifera genotyping. Chardonnay and Cabernet Sauvignon were used as reference cultivars. The markers were combined in multiple sets for simultaneous evaluation of two loci. The total number of different alleles per locus varied from 5 (VVS2, VMD7) to 11 (VVMD5) within the Don cultivars analyzed. The cultivars possessed different sets of allele combinations for loci under study. The genotyping results were subject to cluster analysis. Sibir’kovyi and Pukhlyakovskiy belyi showed the greatest proximity to each other. Molecular studies of local southern Russia grape cultivars will be continued.